Association between intensity of imaging surveillance and clinical outcomes in patients with hepatocellular carcinoma. Issue 151 (June 2022) - Hwang, Jeong Ah; Kang, Tae Wook; Min, Ji Hye; Kim, Young Kon; Kim, Seong Hyun; Sinn, Dong Hyun; Kim, Kyunga
Highlights: Intensive surveillance using CT/MRI was effective in diagnosing very early-stage HCC compared to current standard surveillance. However, intensity of imaging surveillance using CT/MRI did not affect OS. ALBI grade and curative treatment at HCC diagnosis were significant factors for OS. Abstract: Background: The role of computed tomography (CT)/magnetic resonance imaging (MRI) surveillance for hepatocellular carcinoma (HCC) is unclear. We aimed to determine whether the intensity of imaging surveillance using CT and MRI is associated with tumor stage at diagnosis or survival in patients with HCC. Methods: This retrospective cohort study included 529 patients with newly diagnosed HCC under regular surveillance (twice a year testing) at a tertiary academic center. All patients were divided into a standard surveillance group (n = 62; ultrasonography [US] with alpha-fetoprotein) and an intensive imaging surveillance group (US and CT/MRI with alpha-fetoprotein); the latter was divided into a low- (n = 232) and high-intensive (n = 235) imaging surveillance group based on the median percentage of CT/MRI investigations (cut-off, 27%). Relationship between surveillance imaging, stage of HCC at diagnosis, and overall survival (OS) were analyzed. Results: The low- and high-intensive imaging surveillance groups (odds ratio [OR], 0.44; 95% confidence interval [CI], 0.20–0.95; p  = 0.034 and OR, 0.40; 95% CI, 0.19–0.86; p  = 0.014, respectively) had better performances than the standard surveillance group to detect very early-stage HCC. OS was associated with albumin-bilirubin grade (hazard ratio [HR], 1.98; 95% CI, 1.28–3.07; p  < 0.001 for grade 2 and HR, 3.03; 95% CI, 1.11–8.30; p  = 0.027 for grade 3) and the applicability of curative treatment (HR, 2.34; 95% CI, 1.63–3.36; p  < 0.001). However, surveillance intensity did not affect OS ( p  > 0.05). Conclusions: Imaging surveillance for HCC using alternative CT/MRI in addition to US compared to standard practice of US only facilitates the diagnosis of very early-stage HCC but may not improve OS.